Immunohistochemical studies of stellate cells in experimental cholestasis in newborn and adult rats (Clinics, 2008)
BACKGROUND AND AIMS: Although there is much known about liver diseases, some aspects remain unclear, such as the nature of the differences between the diseases observed in newborn infants and those in adults. For example, how do newborns respond to duct epithelial cell injury? Do the stellate cells in newborns respond similarly to those in adults during biliary obstruction? METHODS: Ninety newborn Wistar rats aged six days, weighing 8.0 - 13.9 g each, and 90 adult rats weighing 199.7 - 357.0 g each, were submitted to bile duct ligation. After surgery, they were randomly divided and sacrificed on the 3rd, 5th, 7th, 14th, 21st or 28th day post-bile duct ligation. Hepatic biopsies were obtained and immunohistochemical semi-quantification of desmin and α-SMA expression was performed in hepatic stellate cells and in myofibroblasts in the portal space, and between the portal space and the liver lobule. RESULTS: Desmin expression in the myofibroblast cells post-bile duct ligation was higher in young rats, reaching its peak level in a shorter time when compared to the adult animals. The differences between the groups for α-SMA expression were less significant than for desmin. CONCLUSIONS: These findings indicate that there is an increase in the number of collagen-producing myofibroblast cells in young animals, suggesting that there is more intense fibrosis in this population. This finding may explain why young animals with bile duct obstruction experience more intense portal fibrosis that is similar to the pathology observed in the livers of newborns with biliary atresia.